Full-spectrum responsive photocatalytic activity via non-noble metal Bi decorated mulberry-like BiVO4. (30th August 2021) - Bi, Yaxin; Yang, Yanling; Shi, Xiao-Lei; Feng, Lei; Hou, Xiaojiang; Ye, Xiaohui; Zhang, Li; Suo, Guoquan; Lu, Siyu; Chen, Zhi-Gang
Graphical abstract: Highlights: An in-situ synthesis method for non-noble metal Bi decorated mulberry-like BiVO4 ; Bi/BiVO4 exhibits full-spectrum (UV–vis-NIR) responsive photocatalytic activities; Surface plasmon resonance effects of Bi and synergetic effects between Bi and BiVO4 . Density functional theory (DFT) calculation verify the electron transfer mechanism. Abstract: Due to its appropriate bandgap (∼2.4 eV) and efficient light absorption, bismuth vanadate (BiVO4 ) shows promising photocatalysis activity. However, the charge carrier recombination and poor electron transmission often induce poor photocatalytic performance. Herein, we report a new method to in-situ synthesize non-noble metal Bi decorated mulberry-like BiVO4 by a two-step calcination process. Comprehensive characterizations reveal that non-noble metal Bi nanoparticles grown in-situ on BiVO4 result in the red-shift of the absorbance edge, greatly extending the light absorption from the ultraviolet into the near-infrared region. The surface plasmon resonance excitation of Bi nanoparticles and synergetic effects between Bi and BiVO4 effectively improve the photocatalytic efficiency and promote the separation of photoinduced electron-hole pairs in mulberry-like BiVO4 . Density functional theory (DFT) calculation results further verify that the electrons are transferred from Bi to BiVO4 and the formation of OH radical in Bi/BiVO4 is attributed to the lower simulated free energy, which supports our experimental outcomes. This work provides a novel strategy to enhance light absorption and promote efficient solar utilization of photocatalysts for practical applications.